Risks Management and Bank Performance: The Empirical Evidences from Indonesian Conventional and Islamic Banks - Saiful, Saiful; Ayu, Dea Puspita (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to examine the influence of credit, liquidity, and operational risk management on performance of Indonesian banks performance. The sample used consisted of 26 conventional banks and 11 sharia banks in period 2012-2016. This study found that credit, and liquidity risks management positively influence Indonesian banks performance that measured by return on asset (ROA) and return on equity (ROE). Meanwhile, this study also found operational risks management positively influence Indonesian banks performance that measured by ROA, ROE, and net interest margin. Keywords: Risk Management, Credit Risk Management, Liquidity Risk Management, Operational Risk Management and Bank Performance JEL Classifications: G33, M21 DOI: https://doi.org/10.32479/ijefi.8078